2012
DOI: 10.1007/s11434-012-5513-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure of iron(III)-containing imidazolium salts and their catalytic activity in the alkylation of aryl Grignard reagents

Abstract: A series of iron(III)-containing imidazolium salts of the general formula [DRim] [FeX 4 ] (R = 2,6-diisopropylphenyl, IPr, X = Cl, 1; R = IPr, X = Br, 2; R = tertbutyl, t Bu, X = Cl, 3; R = isopropyl, i Pr, X = Cl, 4; R = benzyl, Bn, X = Cl, 5; R = Bn, X = Br, 6) have been prepared in high yields via reactions of anhydrous ferric halides with equivalent of the corresponding N,N-dihydrocarby-limidazolium halides, where 2-6 are novel ones. All of the complexes were characterized by elemental analysis, Raman spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Six different iron(III)-containing imidazolium salts of the type shown in Figure have been synthesized and studied for the model transformation: a reaction of cyclohexyl bromide and p -tolylmagnesium bromide . While all iron-containing imidazolium salts gave high to excellent conversions, it could be shown that the efficiency of the catalyst can be adjusted by modification of the substituents at the imidazole ring.…”
Section: Substitution Reactionsmentioning
confidence: 99%
“…Six different iron(III)-containing imidazolium salts of the type shown in Figure have been synthesized and studied for the model transformation: a reaction of cyclohexyl bromide and p -tolylmagnesium bromide . While all iron-containing imidazolium salts gave high to excellent conversions, it could be shown that the efficiency of the catalyst can be adjusted by modification of the substituents at the imidazole ring.…”
Section: Substitution Reactionsmentioning
confidence: 99%
“…Synthesis of iron-containing magnetic ionic liquids. In this research, three kinds of iron-containing magnetic ionic liquids were synthesized, which were non-hygroscopic and air-stable [8]. They were [bmim]FeCl 4 , [bPy]FeCl 4 and [bmP]FeCl 4 .…”
Section: Experimental Sectionsmentioning
confidence: 99%
“…In a continuation of our work focused on the development of Fe(III)-containing imidazolium ILs for use in the cross-coupling of aryl Grignard reagents with alkyl halides [9][10][11][12], we report here on the use of ether-functionalized imidazolium salts in the facile synthesis of a series of Fe(III)-containing ILs 1-6, and their use as catalysts in cross-coupling the aryl Grignard with alkyl halides with -hydrogens. Ether-functionalized imidazolium salts have demonstrated attractive physicochemical properties for particular applications, e.g.…”
mentioning
confidence: 99%